REPRESENTASI NILAI-NILAI PENDIDIKAN KARAKTER DALAM NOVEL ANTARA CINTA DAN RIDHA UMMI KARYA ASMA NADIA (KAJIAN THOMAS LICKONA) - Gerry Kusiyu; Elsa Mulya Karlina (CV. ADIBA ASIHA AMIRA, 2026)
This study is motivated by the importance of character education in shaping individuals with noble character, responsibility, and the ability to make decisions based on moral values. Literary works, particularly novels, can serve as an effective medium for instilling these values. This study aims to describe the representation of character education values in the novel Antara Cinta dan Ridha Ummi by Asma Nadia based on Thomas Lickona’s theory of character education. This research employed a qualitative approach using a library research method. The primary data source was the novel Antara Cinta dan Ridha Ummi by Asma Nadia, while secondary data were obtained from books, scientific journals, and other relevant references. Data were collected through reading, note-taking, and documentation techniques and analyzed using descriptive qualitative analysis. The findings reveal that the novel represents the three main components of character education proposed by Thomas Lickona, namely moral knowing, moral feeling, and moral action. The representation of moral knowing is reflected through moral awareness, understanding of moral values, perspective taking, moral reasoning, decision making, and self-knowledge. Meanwhile, moral feeling is represented through conscience, self-esteem, empathy, loving the good, self-control, and humility. Furthermore, moral action is demonstrated through moral competence, moral will, and moral habit as reflected in the characters’ daily lives. Therefore, Antara Cinta dan Ridha Ummi is not only an entertaining literary work but also an effective medium for character education that promotes religious, moral, and social values relevant to contemporary society.